Efektivitas Pemberian Pakan Yang Mengandung Minyak Ikan dan Olahanya Terhadap Fermentasi Rumen Secara In Vitro - Amri, Ulil; Y, Yurleni (Fakultas Peternakan Universitas Jambi, 2014)
Â This experiment was aimed to investigate the effect of ration containing fish oil and its processed on in vitro rumen fermentation. The protected fatty acidâ€™s was in the form of dried carboxylate salt mixture (DCM). The data were analyzed using a completely randomized design with 2x2 factorial models; feeding trial (non CGKK, with CGKK and with fish oil) as the first factor and rumen liquor as second factor (the origin of buffaloes and cattle). The results showed that no interaction was found between the two factors on all parameters. The supplementation with DCM had significantly higher dry matter and organic matter digestibilities. Rumen NH3 of buffalo was lower compared to those of cattle. It is concluded that DCM supplementation does not disturb rumen fermentation.